2001
DOI: 10.1007/s002640100293
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic effect of methotrexate loaded bone cement on osteosarcoma cell lines

Abstract: We mixed various amounts of methotrexate with bone cement and measured the absorbance daily for 4 weeks. The cytotoxic effects on SaOS2 and MG63 osteosarcoma cells were examined by the MTT assay, and analysed according to the methotrexate concentration and the elapsed time. The amount of eluted methotrexate was greatest during the first day, and then decreased rapidly reaching a plateau in the third week. The number of viable tumour cells decreased significantly after 72 h, and they were hardly seen after 1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Hernigou et al [1] reported for the first time that cement implants containing MTX were able to release the drug for a period of months. Subsequent detailed in vitro works evaluated elution kinetics of MTX from the cement pellets [2,4,5]. All authors reported the greatest elution during the first day for all concentrations, with rapid decrease during the following days, and stabilisation to a constant rate of release after two weeks of incubation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hernigou et al [1] reported for the first time that cement implants containing MTX were able to release the drug for a period of months. Subsequent detailed in vitro works evaluated elution kinetics of MTX from the cement pellets [2,4,5]. All authors reported the greatest elution during the first day for all concentrations, with rapid decrease during the following days, and stabilisation to a constant rate of release after two weeks of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Kim at al. [5] showed that the mean amount of MTX eluted from pellet over a 28-day period ranged from 7.2% to 11.7%. Our data were similar and suggested that the majority of the MTX remained in the bone cement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations